A study of the vocabulary and topics of the environment and pollution subject in school curricula and the College of Pharmacy in Iraq - Fadhil, Nada Allawi; Mohamed, Zahraa Saadi Jasim; Hashem, Alyaa Fadhil Saeed; Jebril, Nadia Mahmoud Tawfiq; Kadhim, Aya Lazim; Hassan, Hawraa Majid; AL-Saadi, Hind Hassan Fadhil (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
Iraq is one of the countries affected by climate change, which can be combated by enhancing environmental awareness among citizens and school students. On the other hand, since expired and unused medicines have a negative impact on the environment, raising awareness among pharmacy professionals and including environmental curricula in Pharmacy colleges is very important. Therefore, this study aimed to examine the curricula of the primary and secondary levels in terms of whether they include the subject of environment and pollution, and the curricula of the College of Pharmacy, University of Babylon in terms of whether they include the subject of environment. Science and social studies (for primary stages, from year 1 to 6), chemistry, physics, biology and social studies (for intermediate stages from year 7 to 9), and chemistry, physics and biology (for preparatory stages from year 10 to 12) were chosen, in addition to the Islamic subject, since some Islamic legislations urge the preservation of natural resources and not to waste them. Also, only scientific specialization was relied upon in the preparatory stage (year 11). Pharmacists for Bachelor stages from years 1 to 5 were chosen. The results indicate that the second grade of primary school does not include any curricula related to the environment. As for the first, third and fourth years, there are some topics in the science subject and the science and social studies subject. As for the Islamic subject, there may be a concept related to agriculture and one of the goals of sustainable development in the year 6 of primary school. As for the intermediate stage, year 9 does not have any topics related to the environment and pollution. The first intermediate (year 7) has concepts in biology and social studies, while the second intermediate (year 8) has more extensive or in-depth topics in this field. As for chemistry and physics, there is nothing related to that. The years 11 and 12 do not have topics related to that, while the year 10 is biology only and includes those topics in detail. As for chemistry, physics and Islamic studies, they do not include any of these concepts in the preparatory stage. In terms of College of Pharmacy, Bachelor’s stages do not contain the subject of the environment/ecology. In conclusion, an appropriate curriculum will contribute to building students’ more sustainable performance and a complete sympathy for the sustainable development in their regions.